(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
The ranging of lichens among classes of poleotolerance were made. The most widely spread species from each class are mentioned. The estimation of the ecological state of air environment of the city of Pskov with lichens was held.